2015
DOI: 10.1111/zph.12240
|View full text |Cite
|
Sign up to set email alerts
|

Government Response to the Discovery of a Rabies Virus Reservoir Species on a Previously Designated Rabies‐Free Island, Taiwan, 1999–2014

Abstract: Summary Taiwan had been considered rabies free since 1961. In 2013, Taiwan confirmed the detection of rabies virus in wild Taiwan ferret‐badgers. Up to December 2014, there have been 423 rabies‐confirmed ferret‐badgers and three cases of spillover infection into non‐reservoir hosts. Genetic analysis indicates that TFBV is distinct from all other known rabies virus variants. To date, ferret‐badger rabies is known to occur only in China and Taiwan. The temporal dynamics of rabid ferret‐badgers in Taiwan suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 4 publications
(4 reference statements)
0
22
0
Order By: Relevance
“…Although RABV is usually maintained in distinct host species-associated transmission cycles, typically within the Carnivora and Chiroptera 57 , host shift events are still of public health concern due to increasing risks of human exposures 7 . Recent host shifts between carnivores include the re-emergence of RABV in wild Taiwan ferret-badgers 8 , as well as the outbreaks of domestic dog-associated RABV in Ethiopian wolves 9 and of striped skunk-associated RABV in gray foxes in California 10 . It has also been reported that multiple host shifts between bat and mesocarnivores have occurred with the big brown bat-associated RABV in Arizona 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Although RABV is usually maintained in distinct host species-associated transmission cycles, typically within the Carnivora and Chiroptera 57 , host shift events are still of public health concern due to increasing risks of human exposures 7 . Recent host shifts between carnivores include the re-emergence of RABV in wild Taiwan ferret-badgers 8 , as well as the outbreaks of domestic dog-associated RABV in Ethiopian wolves 9 and of striped skunk-associated RABV in gray foxes in California 10 . It has also been reported that multiple host shifts between bat and mesocarnivores have occurred with the big brown bat-associated RABV in Arizona 11 .…”
Section: Introductionmentioning
confidence: 99%
“…These two epidemic areas are considered as two independent groups in epidemiology [2] as well as in phylogeny of nucleoprotein and glycoprotein genes [16]. This study is the research results of the east epidemic area.…”
Section: Discussionmentioning
confidence: 99%
“…Ferret badger (Melogale moschata) is the sole reservoir host for the rabies virus, and the epidemic is only prevalent in Taiwan Island [1,2]. Epidemiologically, it is indicated that there were the Main (West) and East epidemic areas separated by the Central Mountain Ranges [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malaysia also adopts a dog vaccination policy building a 50 to 80 km immune belt along the border with Thailand; the country had been declared rabies-free since 2012 until 2015 when the disease was introduced most probably from Thailand [9]. Taiwan enforces rabies vaccination in both domestic dogs and cats, and had been rabies-free since 1961 until an epizootic of Chinese ferret-badger started in 2013 [10].…”
Section: Introductionmentioning
confidence: 99%